1992
DOI: 10.1128/iai.60.7.2565-2571.1992
|View full text |Cite
|
Sign up to set email alerts
|

An 80-kilodalton antigen from Histoplasma capsulatum that has homology to heat shock protein 70 induces cell-mediated immune responses and protection in mice

Abstract: An extract of the cell wall and cell membrane from Histoplasma capsulatum yeast cells was assayed by Western blot (immunoblot) for reactivity with two monoclonal antibodies to heat shock protein 70. Four bands with molecular masses of 80, 66, 54, and 32 kDa bound both antibodies. The 80-kDa protein was isolated, analyzed for homology to heat shock protein 70, and tested for antigenicity and immunogenicity in C57BL/6 mice. The 80-kDa protein reacted with monoclonal antibody to heat shock protein 70. Sera from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…In Helicobacter pylori, hsp60 has been considered as a potential candidate for a subunit vaccine (Sharma et al, 1997) and a long-lasting antibody response to hsp60 was demonstrated in animals infected by Brucella abortus (Galdiero et al, 2000). This is consistent with the dominance of hsp60 in infections because of H. capsulatum and C. immitis (Gomez et al, 1992;Maresca & Kobayashi, 1993;Marsh et al, 1998). The role of these molecules as potential vaccines is difficult to assess, as this research is at a preclinical stage.…”
Section: Therapeutic Applications Of Hspssupporting
confidence: 63%
See 1 more Smart Citation
“…In Helicobacter pylori, hsp60 has been considered as a potential candidate for a subunit vaccine (Sharma et al, 1997) and a long-lasting antibody response to hsp60 was demonstrated in animals infected by Brucella abortus (Galdiero et al, 2000). This is consistent with the dominance of hsp60 in infections because of H. capsulatum and C. immitis (Gomez et al, 1992;Maresca & Kobayashi, 1993;Marsh et al, 1998). The role of these molecules as potential vaccines is difficult to assess, as this research is at a preclinical stage.…”
Section: Therapeutic Applications Of Hspssupporting
confidence: 63%
“…The 80-kDa protein was identified by direct amino acid sequencing as homologous to hsp70. Immunization of mice with this antigen produced host resistance to a sublethal but not lethal dose of yeasts (Gomez et al, 1992;Gargano et al, 1995).…”
Section: Histoplasma Capsulatummentioning
confidence: 99%
“…Regarding their antigenicity, while ribosomal protein S18, tubulin, dihydrolipoyl dehydrogenase and putative branched chain amino acid aminotransferase have not been described as antigens on other fungi, enolase, cyclophilin, Mdh, and Hsp70 are well-known antigens in fungi [24][25][26][27][28][29]. In fact, the latter three have also been identified previously as immunodominant antigens of L. prolificans conidia recognized by human IgA [19] and although other antigens, such as enolase, were not detected in the study, this may be due to differences in protein extraction protocol and in spot selection criteria, since in that study antigens were identified according to their relative intensity but not prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hsp70s are thought to play an important role in infections caused by Plasmodium [3], Trypanosoma [4], Schistosoma [5], Leishmania [6], and Mycobacterium [7] species. In the field of fungal pathogens, a member of the hsp70 family of Histoplasma capsulatum was recognized as a target of cellmediated, protective immunity [8] and the hsp70 family of Candida albicans appears to be expressed as both B cell and T cell immunogens in human subjects, with a possible important role in infections caused by C. albicans [9]. Further, the microbial hsp are the antigens of choice for vaccines in various infectious diseases.…”
Section: Introductionmentioning
confidence: 99%